2018
DOI: 10.4236/ojst.2018.84013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disinfectants on Elastic Modulus, Flexural Strength and Color Stability of Denture Base Resins

Abstract: Objective: Infection control protocols dictate the disinfection of dentures. There are no products available which are designed for the specific use of disinfecting dentures. The objective of this study was to investigate the impact of chemical disinfectants on elastic modulus, flexural strength and color stability of denture base resins. Methods: 256 specimens from four acrylic denture base resins were manufactured. Two cold-curing denture base resins: PalaXpress (Heraeus Kulzer, Hanau, Germany), Futura Gen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The specimens immersed in CNF-NB-C (0.05, 0.10 and 0.20 wt%) and CNF-BB-A (0.05 and 0.10 wt%) solutions showed significantly higher values of flexural modulus when compared to those in the other groups, especially the blank and control groups. Some researchers reported that the immersing solutions (especially for disinfection) exerted no significant effects on flexural/elastic modulus after immersion when compared to distilled water 33,34) . A previous study suggested that the denture base material has a lower flexural/elastic modulus, and can release high forces on to the underlying mucosa thereby irritating the gingival tissues and promoting the resorption of the residual alveolar ridge 35) .…”
Section: Discussionmentioning
confidence: 99%
“…The specimens immersed in CNF-NB-C (0.05, 0.10 and 0.20 wt%) and CNF-BB-A (0.05 and 0.10 wt%) solutions showed significantly higher values of flexural modulus when compared to those in the other groups, especially the blank and control groups. Some researchers reported that the immersing solutions (especially for disinfection) exerted no significant effects on flexural/elastic modulus after immersion when compared to distilled water 33,34) . A previous study suggested that the denture base material has a lower flexural/elastic modulus, and can release high forces on to the underlying mucosa thereby irritating the gingival tissues and promoting the resorption of the residual alveolar ridge 35) .…”
Section: Discussionmentioning
confidence: 99%
“…A greater awareness of childhood psychology as well as demand from parents has led practitioners to offer aesthetic PCs. It has been shown that disinfectants can modify the colour stability of denture base resins (Bensel et al 2018 ). Similarly, persistent thermocycling of monolithic zirconia can produce significant colour and translucency changes (Koseoglu et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%